Evaluasi Proses Penyampaian KIE Pencegahan HIV/AIDS Yang Dilakukan ASA PKBI Jawa Tengah Bagi Remaja Di Kota Semarang - Trixie Salawati; Bagoes Widjanarko; Tandiyo Pradekso (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background : The ASA IPPA Central Java has been conducting a series of IEC activities of HIV prevention programmes for young people regularly. These activities are conducted by ASA volunteers by providing a lecture to middle and high school students. Unfortunately, these activities have never been evaluated in terms of the methods, the materials and theoutputs of the lecture. This study observes the IEC process of HIV prevention for young people conducted by ASA volunteers.Method : An observation technique using check lists has been used to observe the process of the IEC activities which were conducted by the ASA volunteers. The performance of the communicators, the curriculum provided, the responses of the target group and the media used, were observed directly during the IEC activities. Focus group discussions with students and indepth interviews with coordinators of IEC activities in each school, were also conducted to obtain more detail information. Two middle schools and three high schools which selected purposively have been participated in this study.Results : The study shows that the performance of the communicators during the IEC activities were relatively good, particularly in terms of language, skills of communication technique and relationship with the audiences. Although not all questions asked by the audiences, havebeen answered by the communicators, particularly unrelated topics to HIV/AIDS and drugs, using new terminology during a lecture has made many students interested to listen and provided some good responses. In terms of the IEC materials, the middle schools were more focused on drugs, whereas the high schools were more concerned in HIV/AIDS prevention. Each lecture provides an additional programmes such as HIV/AIDS film and drug user cases in VCD format. This study suggests that the skills of communicators and the materials of the IEC, should be improved regularly in order to increase the fit between the IEC activities and the audience needs. The usage of audio visual aids during the IEC process should be optimized to make it easier for the audiences to understand the materials being provided. The output assessments should also be conducted in order to obtain direct feed back from the audiences.Keywords: IEC process, HIV/AIDS, Students.